PENGARUH KUALITAS PRODUK DAN NILAI PELANGGAN TERHADAP LOYALITAS PELANGGAN ES MAHKOTA DI KOTA PALU - MAULANA, AAN (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2017)
This research intends to identify and to analyze the effect of product quality and customer value of customer of Es Mahkota in Palu City, the effectof product quality of customer of Es Mahkota in Palu City. This quantitave research show relation between variables. Population of this research is the customer of Es Mahkota in Palu City that has consumed the product for three to four times. 90 samples as respondent was taken through purposive sample. Data were collected using questionnarie and analyzed through multiple linear regression using the application of SPSS release 20. The result of this research revealed that product quality and customer value affects the loyality of cuetomer of Es Mahkota in Palu City, product quality affects the loyality of customer of Es Mahkota in palu City, and customer value affects the loyality of customer of Es Mahkota in Palu City.